Storms - Goin, Miriam (Washington, D.C. : National Geographic, 2009)
Photographs and text introduce early readers to various types of storms and examine the conditions and effects of thunder and lightning, monsoons, hurricanes, and tornadoes.
Weather! -- Thunder and lightning -- Hailstorm -- Tornado -- Sandstorm -- Blizzard -- Monsoon -- Hurricane -- Out of this world! -- Guess! -- House for a storm -- Wild animals, wild weather -- Glossary.
"National Geographic Kids"--Cover.
Booklist.
Horn Book.
Library Media Connection.
Booklist, December 2009.
Horn Book, October 2009.
Keywords: Storms -- Juvenile literature; Storms; Storms; Readers (Elementary).